Vulnerability evaluation and prediction of the water-energy-food-ecology nexus in the Yangtze River Economic Belt based on TOPSIS, neighborhood rough set and support vector machine - Pan, Yue; Chen, Yan; Liu, Yue (Frontiers in Environmental Science, 2022)
With the intensification of human activities, the vulnerability of water, energy, food and ecology systems has become more and more prominent, and the research on the vulnerability of the water-energy-food-ecology (WEFE) nexus is significant to realizing regional sustainable development. This study aims to make a comprehensive measurement of the vulnerability of the WEFE nexus in the Yangtze River Economic Belt (YREB) from 2008 to 2019, clarify the evolutionary trend of its vulnerability, and predict the vulnerability of each province (municipality) in the future, to formulate policies to reduce vulnerability. This study firstly constructs a vulnerability evaluation index system of the WEFE nexus based on the VSD framework and uses the neighborhood rough set (NRS) to reduce the attributes. Then, the TOPSIS model is used to evaluate the vulnerability of the WEFE nexus. Finally, by comparing the training accuracy of the random forest, decision tree and support vector machine (SVM) model, the SVM model is selected to predict the vulnerability of the WEFE nexus under different scenarios in 2025. The results show that the vulnerability of the WEFE nexus in the YREB showed a fluctuating downward trend from 2008 to 2019. The decline is faster in the middle and upper reaches, and slower in the lower reaches. In 2025, under a strong resource management scenario, the vulnerability of the provinces (municipalities) in the YREB will decrease significantly, while the weak and moderate resource management scenarios are not conducive to reducing vulnerability and even worsening. Therefore, in the future, the provinces (municipalities) in the upper, middle and lower reaches should make reasonable use of the resource endowments, take measurements actively according to local conditions, and continuously strengthen the management of water, energy, food and ecological resources, thus promoting the continuous improvement of the vulnerability of the WEFE nexus.